MEMBANGUN JARINGAN INTERNET WIFI YANG SEHAT DI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA DAERAH ISTIMEWA YOGYAKARTA - Suryaningrum, Fajar; Suraya, Suraya; Rachmawati K, Yuliana (Jurnal Jarkom, 2013)
ABSTRACTNetwork Wireless Fidelity (Wi-Fi) to access the internet is very much healthy ni installed in offices and at other public places. In some offices that do not have internet security so employees can easily access sites that are not appropriate and can lead to decreased performance of the employee. Therefore, in Education, Youth and Sports Office will be using a healthy method by using multiple Internet applications that is Internet security and DNS Nawala Squid proxy server is implemented. The results of this study will generate healthy netode internet by blocking sites that are considered negative. This method is expected to make a wireless network in Education, Youth and Sports Office to avoid interference that can impair quality sites Internet users.Keywords : Proxy Server, Education, Youth and Sports Office and the Internet Healthy